Water-Energy Nexus: Review of Literature in Management of Integrated Systems, Challenges and Opportunities. Case Study in Urban Context - Silva, Ana Rita Carriço (2017)
In a society where Energy and Water walk side by side in practically all sectors of activity, it becomes necessary to analyze them from a productive, economic and sustainable point of view. From the extraction of mines and wells, to its treatment and transportation, and to the cooling systems of energy production, and despite being independently developed, managed and regulated, it is known that water needs energy and energy needs water. All these concerns, decision-making and the relationship between water and energy by itself create an opportunity to improve management in both sectors. There is an urgent need to consider all the assumptions and alternatives to improve the system and reduce energy consumption, which includes technological modifications and optimized resources management, leading to a more sustainable future. The increasing demand for energy and its exponential trend will have repercussions at all levels and will consequently increase the strain on freshwater resources with the most affected agricultural and industrial sectors. By improving the efficiency of water and energy use, there are positive repercussions that allow for substantial savings, especially where there is a lack of such resources. This article aims to address all these crucial issues related to energy and water in order to increase knowledge on the subject and to help promote alternatives for managing and developing integrated management systems and, consequently, for a rational use of both resources and a more sustainable future.